INFLUENCE OF SOME FLOCCULANTS ON FLOCCULATION EFFICIENCY OF DIATOM Skeletonema costatum - Nhân, Lê Thị Tuyết; Mến, Đào Thị; Trâm, Mạc Hồ Mai; Liên, Nguyễn Thị Thu (Hue University Journal of Science: Natural Science, 2018)
Microalgae cultivation is an indispensable step in aquaculture hatcheries to create a feed source for larval and juvenile aqua-animal species. One of the problems in the production of large-scale microalgal biomass is that it requires appropriate low-cost biomass harvesting techniques. For the purpose of finding the most suitable method for recovering the biomass of Skeletonema costatum in large-scale cultivation, we have determined the influence of some flocculants on the flocculation efficiency. The results of laboratory studies showed that the recovering efficiency of Skeletonema costatum was 74.15 ± 3.85% at pH 10.5 after 1 hour. The optimal biomass recovering rate was 94.66 ± 3.26% and 91.01 ± 4.65% at FeCl3 200 mg/L and FeSO4 100 mg/L after 15 minutes, respectively. In experiments with AlCl3 and Al2(SO4)3, the recovering efficiency was 95.23 ± 2.87% at AlCl3 50 mg/L and 91.34 ± 3.8% at Al2(SO4)3 100mg/L after 30 minutes. In this study, Al2(SO4)3 and AlCl3 gave higher flocculation efficiencies for Skeletonema costatum and slower cell damage compared with FeCl3and FeSO4 or pH adjustment.